Quality of life and clinical characteristics of renal transplant patients with and without chronic rhinosinusitis: Calidad de vida y características clínicas de los pacientes en trasplante renal con y sin rinosinusitis crónica - Andrade-Bonilla, Clotilde Margarita (2024)
Introduction: Transplantation is the treatment of choice in patients with chronic kidney disease (CKD). It requires immunosuppression, which predisposes to the development of complications. Chronic rhinosinusitis (CRS) is one of the most important. Objective: To compare the characteristics of patients with CKD with and without CRS undergoing renal transplantation protocol in a concentration Hospital in Puebla, Mexico. Methods: Comparative, cross-sectional, retrospective study in patients in a tertiary care hospital with CKD and undergoing renal transplantation protocol. The SNOT-22 and Lund-Mackay scales were applied. Descriptive statistics and Mann-Whitney U test, Fisher's exact test and Phi coefficient were used; p<0.05 was considered significant. Results: 360 patients were recruited, 49 presented CRS, prevalence: 13.61%. Means: age: 39.22 ±12.09 years and evolution time: 17.73 ±5.91 weeks. They presented nasosinusal polyposis 14.3%, nasal obstruction 95.9%, facial algia 67.3%, rhinorrhea 49%, hyposmia/anosmia 40.8%. Associated risk factors: allergy to acetylsalicylic acid (p=0.014) and atopy (p=0.000). Anatomical variants in patients with and without CRS, respectively: Agger-Nasi cell 95% and 15.4%, septal deviation 50% and 6.4%, turbinate hypertrophy 50% and 1.3%, concha bullosa 30% and 4.2%, and turbinate paradoxical 10% and 1.6%. Predominant quality of life impairment in patients with and without CRS was moderate (53.1%) and mild (97.1%) respectively (p=0.000). Conclusion: Prevalence of CRS was 13.61%, allergy to acetylsalicylic acid and atopy were associated risk factors; Agger-nasi was predominant anatomical variant. Tomographic severity was mild, and quality of life impairment was moderated.